Hepatoblastoma in a one month infant - a case report - Tomasz Chromiec; Marcin Hetman; Natalia Fornal; Dominik Grzebyk; Ewelina Bracik; Karolina Widłak; Joanna Nurzyńska-Flak; Marta Prządka (Kazimierz Wielki University, 2018)
Introduction: The manifestations and epidemiology of cancer differ between adults and children. Hepatoblastoma is the most common pediatric liver malignancy with multiple risk factors under investigation or already found to be at play. The aim of this work is to give a quick summary of the epidemiology of pediatric cancer with special consideration given to patients in the neonatal period. Case report: A one-month old boy has been admitted to the clinic following an incidental finding of left renal agenesis. Abdomen CT revealed a liver mass that proved to be hepatoblastoma on biopsy. Alpha fetoprotein serum level was found to be elevated. The treatment consisted of right hemihepatectomy and pre- and postoperative, cisplatin-based chemotherapy. Discussion: Hepatoblastoma is an age-specific diagnosis with prognosis that improved significantly in recent decades. Liver malignancy should be suspected in children with physical finding of hepatomegaly and always considered in case of elevated alpha fetoprotein or a liver mass on imaging examinations. An extensive list of risk factors that also include genetic syndromes may aid in identifying children that are at a particularly high risk for developing liver malignancy.